2015
DOI: 10.1089/cap.2014.0071
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Attention-Deficit/Hyperactivity Disorder Drug Consumption in Children and Adolescents in Slovenia from 2001 to 2012: A Drug Use Study from a National Perspective

Abstract: When new drugs are licensed in a jurisdiction, their prescription rates increase rapidly. The changes in the pattern of prescribing medicines are evident in Slovenia, primarily in the increase of OROS-MPH and ATX prescriptions and in the rapid decrease of IR-MPH prescriptions. Results indicate a need for appropriate interventions in Slovenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
4
22
0
Order By: Relevance
“…13,14 However, there has been a very marked rise in the number of prescriptions issued for ADHD medications across high-income countries in the last decade. 15,16,17 Rises in clinic incidence and treatment could simply indicate increased parent and teacher awareness of ADHD and/or changes in impact. 18,19 Nevertheless, European studies have repeatedly found that despite the rise in ADHD treatment, the administrative prevalence is lower than the population figure, highlighting that in these countries there is still under-diagnosis.…”
Section: Epidemiologymentioning
confidence: 99%
“…13,14 However, there has been a very marked rise in the number of prescriptions issued for ADHD medications across high-income countries in the last decade. 15,16,17 Rises in clinic incidence and treatment could simply indicate increased parent and teacher awareness of ADHD and/or changes in impact. 18,19 Nevertheless, European studies have repeatedly found that despite the rise in ADHD treatment, the administrative prevalence is lower than the population figure, highlighting that in these countries there is still under-diagnosis.…”
Section: Epidemiologymentioning
confidence: 99%
“…Currently, it is well known that perinatal complications and neonatal environment (as well as genetic/epigenetic factors) affect child's physical and mental health development (Allen, Lewinsohn & Seeley, ; Appleton et al., ; Johnson, ; Johnson & Marlow, ). Attention deficit and hyperactivity disorder (ADHD) prevalence varies across different studies between 1% and 8% (Polanczyk, Salum, Sugaya, Caye & Rohde, ; Štuhec, Locatelli & Švab, ; Štuhec, Švab & Locatelli, ) and it is caused by gene and environment interplay as reported by most studies (Biederman & Faraone, ; Fitzgerald, Bellgrove & Gill, ; Montiel‐Nava, Peña & Montiel‐Barbero, ). No gender differences have been found in the prevalence of ADHD combined type, including both inattentive and hyperactive‐impulsive symptoms, whereas girls with ADHD show the predominantly inattentive type two times more frequently than boys (Levy, Hay, Bennett & McStephen, ; Staller & Faraone, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in European countries have reported that <3.2% of adults with ADHD receive pharmacotherapy targeting the core symptoms of ADHD,21 although new data are available especially on pharmacoepidemiology, because when new drugs were licensed in a jurisdiction, their prescription rates increased rapidly 29. In contrast, a survey conducted in Southern California reported that 48%–58% of adults who were diagnosed with ADHD received pharmacotherapy for ADHD symptoms 17.…”
Section: Introductionmentioning
confidence: 99%